2022
DOI: 10.1002/admi.202102246
|View full text |Cite
|
Sign up to set email alerts
|

Mechanofluorochromic Material toward a Recoverable Microscale Force Sensor

Abstract: cation of mechanical stimuli such as scratching or grinding, promises applications for force sensors. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Emission changes of coordination complex crystals, [24] polymeric microcrystals, [30] and organic fluorophores, [31][32][33][34][35][36] have been correlated to an applied force or pressure for new anticounterfeiting technologies [23][24][25][26][27][28] and biological stress probes. [29] Force sensing via mechanofluorochromic activity has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Among many luminescent molecules [1–4], organic materials with mechanofluorochromic (MFC) behaviours have attracted numerous interest [5–10] because of their unique potential applications in fields of organic light‐emitting diodes [11], security papers [12], mechano‐sensors [13], and memory devices [14]. To date, a great amount of effort has been devoted to the design and synthesis of materials with MFC characteristics, including the derivatives of isoquinoline [15], tetraphenylethylene [16], carbon nanodots [17], 9,10‐distyrylanthracene [18], azaanthracence [19], naphthalimides [20] and some organic boron‐containing π‐conjugated molecules [7, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Among many luminescent molecules [1–4], organic materials with mechanofluorochromic (MFC) behaviours have attracted numerous interest [5–10] because of their unique potential applications in fields of organic light‐emitting diodes [11], security papers [12], mechano‐sensors [13], and memory devices [14]. To date, a great amount of effort has been devoted to the design and synthesis of materials with MFC characteristics, including the derivatives of isoquinoline [15], tetraphenylethylene [16], carbon nanodots [17], 9,10‐distyrylanthracene [18], azaanthracence [19], naphthalimides [20] and some organic boron‐containing π‐conjugated molecules [7, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the contact force between a cantilever and the surface of a material has enabled the quantitative indenting and scratching of MRL-active molecular microcrystals. Confocal fluorescence microscopy has also facilitated the correlation of the topography of scratched surfaces with the corresponding emission spectra at a sub-μm scale. In 2000, Burns et al first demonstrated the nanoscale shear-induced blue-to-red chromatic transition (red form is also weakly fluorescent) of a polydiacetylene thin film using the AFM tip …”
Section: Sense Deform and Healmentioning
confidence: 99%
“…192 Thus, they take advantage of the switching of light emission by external stimuli, e.g., solvent molecules (solvatofluorochromism, often called solvatochromic luminescence), 193 temperature (thermofluorochromism), 194 electric field (electrofluorochromism), 195 pressure (piezofluorochromism), 196 or mechanical action (mechanofluorochromism). 197 Photochromic luminescence was also realized; in this case, as the light irradiation can be used both as a trigger to switch the state of a material and as the generator of the output signal; thus, to employ such luminescent photochromism in optical devices, the usage of two different wavelengths playing two above-mentioned roles is the most convenient, yet challenging, solution. 198,199 The broad research area within optical materials is also occupied by the materials able to exhibit various nonlinear optical (NLO) properties such as two-photon absorption, second and higher-order harmonic generation (SHG and others), or the optical Kerr effect.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the stimuli-responsive luminescent materials are the emissive analogs of chromic materials, often named fluorochromic systems . Thus, they take advantage of the switching of light emission by external stimuli, e.g., solvent molecules (solvatofluoro­chromism, often called solvatochromic luminescence), temperature (thermofluoro­chromism), electric field (electrofluoro­chromism), pressure (piezofluoro-chromism), or mechanical action (mechanofluoro­chromism) . Photochromic luminescence was also realized; in this case, as the light irradiation can be used both as a trigger to switch the state of a material and as the generator of the output signal; thus, to employ such luminescent photochromism in optical devices, the usage of two different wavelengths playing two above-mentioned roles is the most convenient, yet challenging, solution. , …”
Section: Introductionmentioning
confidence: 99%